Application of the PjBL-STEM Model to Improve Science Literacy of Class XI SMAN Plus Student - Annisa Al Fatihah; Y Yennita (Journal of Indonesian Science Teachers, 2023)
This research aims to improve students' scientific literacy skills by using the Project-based learning (PjBL) learning model integrated with the STEM (science, technology, engineering, and mathematics) approach in class XI MS 3 students at SMAN Plus, Riau Province. The research used the Classroom Action Research (PTK) method with a total of 29 students, which was carried out in two cycles, with each PTK cycle consisting of five steps, namely: 1) localizing the problem, 2) planning, 3) action and observation, 4) analyzing data, and 5) reflection. The scientific literacy studied includes 3 competencies, namely explaining phenomena, interpreting, evaluating, and designing scientific investigations. The results of the analysis of students' scientific literacy abilities from the comparison of cycle I and cycle II showed an increase in scientific literacy scores, namely from 64.3 to 72.1. Based on the research results, it can be concluded that the application of the PjBL-STEM learning model is effective in improving students' scientific literacy skills in learning Physics, especially in class XI MS 3 SMA Plus Pekanbaru.